Pressure and Temperature Effects on Stoichiometry and Microstructure of Nitrogen-Rich TiN Thin Films Synthesized via Reactive Magnetron DC-Sputtering. (28th January 2008) - Penilla, E.; Wang, J.
Abstract : Nitrogen-rich titanium nitride (TiN) thin films containing excess nitrogen up to 87.0 at.% were produced on (100) Si substrates via the reactive magnetron DC-sputtering of a commercially available 99.995 at.% pure Ti target within an argon-nitrogen (Ar-N 2 ) atmosphere with a 20-to-1 gas ratio. The process pressure (P P ) and substrate temperature (T S ) at which deposition occurred were varied systematically between 0.26 Pa–1.60 Pa and between15 .0 ∘ C–600 ∘ C, respectively, and their effects on the chemical composition, surface morphology, and preferred orientation were characterized by energy dispersive X-ray spectroscopy (EDS), field emission scanning electron microscopy (FE-SEM), and X-ray diffraction (XRD). The EDS analysis confirms increasing nitrogen content with increasingP P andT S . The SEM images reveal a uniform and crystallized surface morphology as well as a closely packed cross-sectional morphology for all crystalline films and a loosely packed cross-sectional morphology for amorphous films. Films produced at lowerP P andT S have a pyramidal surface morphology which transitions to a columnar and stratified structure asP P andT S increase. The XRD analysis confirms the existence of only theδ -TiN phase and the absence of other nitrides, oxides, and/or sillicides in all cases. It also indicates that at lowerP P andT S, the preferred orientation relative to the substrate is along the (111) planes, and that it transitions to a random orientation along the (200), (220), and (311) planes asP P andT S increase and these results correlate with and qualify those observed by SEM.